Pharmacists implementing transitions of care in inpatient, ambulatory and community practice settings - Sen S; Bowen JF; Ganetsky VS; Hadley D; Melody K; Otsuka S; Vanmali R; Thomas T (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: To introduce pharmacists to the process, challenges, and opportunities of creating transitions of care (TOC) models in the inpatient, ambulatory, and community practice settings. Methods: TOC literature and resources were obtained through searching PubMed, Ovid, and GoogleScholar. The pharmacist clinicians, who are the authors in this manuscript are reporting their experiences in the development, implementation of, and practice within the TOC models. Results: Pharmacists are an essential part of the multidisciplinary team and play a key role in providing care to patients as they move between health care settings or from a health care setting to home. Pharmacists can participate in many aspects of the inpatient, ambulatory care, and community pharmacy practice settings to implement and ensure optimal TOC processes. This article describes establishing the pharmacist's TOC role and practicing within multiple health care settings. In these models, pharmacists focus on medication reconciliation, discharge counseling, and optimization of medications. Additionally, a checklist has been created to assist other pharmacists in developing the pharmacist's TOC roles in a practice environment or incorporating more TOC elements in their practice setting. Conclusion: Optimizing the TOC process, reducing medication errors, and preventing adverse events are important focus areas in the current health care system, as emphasized by The Joint Commission and other health care organizations. Pharmacists have the unique opportunity and skillset to develop and participate in TOC processes that will enhance medication safety and improve patient care.